2018
DOI: 10.4132/jptm.2017.11.21
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous Mucinous Carcinoma with Extramammary Paget’s Disease: Eccrine or Apocrine?

Abstract: Primary cutaneous mucinous carcinoma (PCMC) is an uncommon tumor of the sweat gland origin. The occurrence of PCMC is mostly in middle-aged and older patients, with a slight male predominance. Most cases of PCMC arise on the head, with a preference for eyelids. The histogenesis of PCMC, whether eccrine or apocrine, remains controversial. We report a rare case of PCMC with secondary extramammary Paget’s disease in the groin of a 75-year-old man, which favored an apocrine origin. Furthermore, based on a review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Furthermore, the PCMC is mostly reported in middle-aged and older individuals [ 8 ] with a 2:1 predominance in men as compared to women [ 1 ]. The neoplasm also has an increased predilection to white rather than individuals of African American, Asian, or Indian ethnicities [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the PCMC is mostly reported in middle-aged and older individuals [ 8 ] with a 2:1 predominance in men as compared to women [ 1 ]. The neoplasm also has an increased predilection to white rather than individuals of African American, Asian, or Indian ethnicities [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, the clinical presentation of PCMC is known to be non-specific with differential diagnoses including lacrimal sac tumor, sebaceous carcinoma, melanoma, pyogenic granuloma, epidermoid cyst, lipoma, pilomatricoma, neuroma, cystic basal cell carcinoma, and metastatic adenocarcinoma [ 6 , 7 ]. According to Oh and Kim [ 8 ], there is controversy surrounding the histogenesis of PCMC. While several studies report the neoplasm to have shown an eccrine differentiation [ 9 , 10 ], several others reported an apocrine origin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Infrequently, the lesion can form an indurated plaque in the epidermis that is larger than the underlying mass in the dermis. 12 The average tumor size at initial presentation based on the SEER Database analysis was 1.63 cm, with most tumors being less than 3 to 4 cm. However, lesions as large as 20 cm have been reported.…”
Section: Clinical Presentationmentioning
confidence: 97%
“…2,5,8 Primary cutaneous mucinous carcinoma has a very distinctive appearance under the microscope, with nest and cords of cuboidal epithelial cells floating in pools of extracellular mucin, sometimes with extension into the subcutaneous fat. 9,12,13 Given the low number of cases in the literature, there are no established treatment guidelines for PCMC, leaving clinicians to rely on retrospective case series to better understand how to appropriately manage these patients. 2,14 The potential for local recurrence and subsequent unresponsiveness to radiation and chemotherapy warrant complete excision of the clinical lesion with margin control.…”
mentioning
confidence: 99%